Remittances and the Brain Drain: Evidence from Microdata for Sub-Saharan Africa - Julia Bredtmann; Fernanda Martínez Flores; Sebastian Otten (The Journal of Development Studies, 2018)
Based on unique microdata from five Sub-Saharan African countries that contain comprehensive information on both migrants and their households at the origin country, we investigate the effect of migrants' education on their remittance behaviour. Our results reveal that migrants' education has no impact on the likelihood of sending remittances, but a positive effect on the amount of money sent, conditional on remitting. The latter effect holds for internal migrants and migrants in non-OECD countries, while it vanishes for migrants in OECD destination countries once characteristics of the origin household are controlled for.
Keywords: 330